"You knit me together in my mother's womb": a theology of creation and divine action in light of intersex. Issue 2 (4th May 2018) - Raby, Elyse J.
ABSTRACT: Some Christian theologians and intersex Christians maintain that intersex is part of God's good and intended creation, in contrast to those who view intersex as a pathological result of fallen nature. The former claim that intersex bodies "are how God made them" and that "God does not make mistakes;" however, these statements risk implying a belief in special creation or divine intervention, two theological positions which have been challenged by evolutionary theory and contemporary natural sciences. This paper provides a more nuanced theology of creation and divine action as a foundation for a positive theology of intersex. Drawing from the work of Thomas Aquinas on primary and secondary causality, the author argues that God, as primary cause, creates the intersex person through the free interplay of secondary causes, in the same way and to the same extent that God acts in the creation of every other person.